[Afisz. Incipit] Rolnicy! Stawajcie do współzawodnictwa o wysoki plon. (Gdańsk : [wydawca nieznany], 1948)
Sztrajfa propagandowa.
Keywords: Propaganda -- Polska -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1990.